PENERAPAN MOORA PADA PEMBERIAN KEPUTUSAN PREDIKAT SANTRI TELADAN - Indahini, Sri; Nofriadi, Nofriadi; Kifti, Wan Mariatul (JISTech (Journal of Islamic Science and Technology), 2023)
Darul Hikma Islamic Boarding School is one of the Islamic boarding schools in Asahan Regency. The teaching and learning process at this Islamic boarding school is based on an established curriculum and religious knowledge. However, determining the achievements of exemplary students experiences difficulties. This is because the process carried out is still carried out using formula calculations. Apart from that, there are many data errors due to the large number of criteria being assessed. The aim of this research is to help Islamic boarding school managers determine exemplary students by building a decision support system using the MOORA method. So with this system, managers only input every value obtained by students is entered directly into the system. The input value will be processed automatically by the system so that you can get results quickly, precisely and accurately